Carta de E. González Mena a Rafael Arjona Siaca - González Mena, E.; Arjona Siaca, Rafael (My University, 1923)
Carta relacionada a viaje de José Tous Soto a Washington,D.C.
Keywords: González Mena, E.--Correspondencia.; González Mena, E.--Correspondence.; Arjona Siaca, Rafael--Correspondence.; Arjona Siaca, Rafael--Correspondencia.